Information and communication technology integration and teaching mathematics in higher education - Tokanov, Mansur; Damekova, Saule; Kuttykozhayeva, Shakharzat; Abdoldinova, Gulsim; Smagulov, Yessengali (Journal on Mathematics Education, 2022)
The purpose of the study is to develop a model for the application of information and communication technology in the teaching of higher mathematics at the level of school education. The leading method for studying this issue is testing developed by V.E. Milman "Diagnostics of motivational structure of personality", which allows studying the level and features of motivational sphere of the researched based on characteristics of their personality with prevailing emotional background of interest, which are directly connected with motivational sphere and due to which it is possible to influence the level of motivation and mastering of the material on topics of higher mathematics based on given parameters of its increase. The identified indicators enable determining the success of using information and communication technologies within the framework of the created model improving the educational process of studying elements of higher mathematics at school. This will enable students to understand how the knowledge they are learning will be put into practice in their lives in the future, allowing them to be highly motivated in their approach to learning the subject, as well as within the framework of imaginative reconstructions of mathematical figures from different angles, graphs of various parameters, imaginative explanations of formulae, theorems and mathematical rules, which will be displayed in 3D on a large screen, thus enabling students, through their visualization, to understand their essence from different perspectives, which will be reinforced by their practical application.